Botrytis cinerea PMT4 Is Involved in O-Glycosylation, Cell Wall Organization, Membrane Integrity, and Virulence - Verónica Plaza; Alice Pasten; Luz A. López-Ramírez; Héctor M. Mora-Montes; Julia Rubio-Astudillo; Evelyn Silva-Moreno; Luis Castillo (Journal of Fungi)
Proteins found within the fungal cell wall usually contain both N- and O-oligosaccharides. N-glycosylation is the process where these oligosaccharides (hereinafter: glycans) are attached to asparagine residues, while in O-glycosylation the glycans are covalently bound to serine or threonine residues. The PMT family is grouped into PMT1, PMT2, and PMT4 subfamilies. Using bioinformatics analysis within the Botrytis cinerea genome database, an ortholog to Saccharomyces cerevisiae Pmt4 and other fungal species was identified. The aim of this study was to assess the relevance of the bcpmt4 gene in B. cinerea glycosylation. For this purpose, the bcpmt4 gene was disrupted by homologous recombination in the B05.10 strain using a hygromycin B resistance cassette. Expression of bcpmt4 in S. cerevisiae ΔScpmt4 or ΔScpmt3 null mutants restored glycan levels like those observed in the parental strain. The phenotypic analysis showed that Δbcpmt4 null mutants exhibited significant changes in hyphal cell wall composition, including reduced mannan levels and increased amounts of chitin and glucan. Furthermore, the loss of bcpmt4 led to decreased glycosylation of glycoproteins in the B. cinerea cell wall. The null mutant lacking PMT4 was hypersensitive to a range of cell wall perturbing agents, antifungal drugs, and high hydrostatic pressure. Thus, in addition to their role in glycosylation, the PMT4 is required to virulence, biofilm formation, and membrane integrity. This study adds to our knowledge of the role of the B. cinerea bcpmt4 gene, which is involved in glycosylation and cell biology, cell wall formation, and antifungal response.